2019
DOI: 10.1007/s10734-019-00388-2
|View full text |Cite
|
Sign up to set email alerts
|

Professional support staff in higher education: networks and associations as sense givers

Abstract: The aim of this study is to explore the functions that professional networks could have as sense givers during the process in which professional support staff at higher education institutions make sense of their roles. The empirical data comprise interviews with three categories of support staff at three technical universities in Sweden and a review of home pages and other written sources from ten, both Swedish and international, professional networks. One conclusion is that the networks can serve as sense giv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 28 publications
(51 reference statements)
0
5
0
2
Order By: Relevance
“…La literatura ha comenzado a identificar a los funcionarios como un "stakeholder" interno, al igual que los estudiantes, profesores y autoridades (Aarrevaara & Dobson, 2013, pp. 161-163;Adler & Lalonde, 2019, p. 75;Leiber, 2016, p. 18;Ryttberg & Geschwind, 2019, p. 1065; es decir, como un grupo de interés con influencia en la definición de objetivos organizacionales (Freeman, 1984). Producto de ello, algunos autores han empezado a conceptualizar la universidad como una organización "multiprofesional" (Schneijderberg, 2017, p. 2), otros a llamarla "All-Administrative University" (Ginsberg, 2013).…”
Section: D) Implicancias Organizacionales De La Burocratizaciónunclassified
See 1 more Smart Citation
“…La literatura ha comenzado a identificar a los funcionarios como un "stakeholder" interno, al igual que los estudiantes, profesores y autoridades (Aarrevaara & Dobson, 2013, pp. 161-163;Adler & Lalonde, 2019, p. 75;Leiber, 2016, p. 18;Ryttberg & Geschwind, 2019, p. 1065; es decir, como un grupo de interés con influencia en la definición de objetivos organizacionales (Freeman, 1984). Producto de ello, algunos autores han empezado a conceptualizar la universidad como una organización "multiprofesional" (Schneijderberg, 2017, p. 2), otros a llamarla "All-Administrative University" (Ginsberg, 2013).…”
Section: D) Implicancias Organizacionales De La Burocratizaciónunclassified
“…Una vez que ciertas estructuras y rutinas administrativas son establecidas, éstas son adoptadas en la red de funcionarios universitarios (Gornitzka et al, 1998, p. 38). Estos conforman asociaciones de alcance internacional, en las que intercambian experiencias y construyen elementos identitarios (Graham, 2009, p. 179;Ryttberg & Geschwind, 2019). La modificación de las misiones institucionales, como emulación de universidades percibidas como exitosas, probablemente ha desatado procesos de isomorfismo mimético, aumentando a su vez las funciones administrativas (Baltaru, 2019, p. 643).…”
unclassified
“…This is a concept used when exploring groups of staff at HEIs who do not fit the conventional binary descriptors of "academics" or "non-academics" […]' (Ryttberg, 2020) • 'Their functions typically require highly educated specialists and experts in specific areas of administration […]. Furthermore, they do not identify themselves with the term administrator […], which refers to functions that are more clerical or secretarial […]' (Ryttberg & Geschwind, 2019) • Not explicitly defined or described in reviewed document (Ryttberg & Geschwind, 2017) Third space professional…”
Section: Professional Support Staffmentioning
confidence: 99%
“…Identity and policymaking related issues are absent in these works so it is important to expand the scope of investigation. Ryttberg and Geschwind (2019) aim to understand the role of support staff's networks as sense givers. They found that associations providing trainings, courses, or even certificates can contribute in the long run to 'creating common understanding of specific roles, supporting the delineation of the specificities or scripts of the role of the professional staff' (Ryttberg & Geschwind, 2019, p. 14).…”
Section: Literature Reviewmentioning
confidence: 99%